Highly efficient and stable blue-emitting CsPbBr3@SiO2 nanospheres through low temperature synthesis for nanoprinting and WLED. (15th May 2018) - Shao, He; Bai, Xue; Pan, Gencai; Cui, Haining; Zhu, Jinyang; Zhai, Yue; Liu, Jingshi; Dong, Biao; Xu, Lin; Song, Hongwei
Abstract: Inorganic perovskite quantum dots (QDs) have attracted wide attention in display and solid-state lighting because of their easily tunable band-gaps and high photoluminescence quantum yields (PLQY) of green light emission. However, some drawbacks limit their practical applications, including the low PLQY of blue light emission and the instability in the moisture environment. In this work, efficient blue-light emitting CsPbBr3 perovskite QDs with PLQY of 72% were developed through a bandgap engineering approach. The achieved blue-light emitting PLQY is much higher than the values acquired in the inorganic perovskite QDs in the literature. And the emission color of the as-prepared QDs can be facially tuned by only adjusting the reaction temperature. Further, the mono-dispersed perovskite QDs@SiO2 composites were constructed benefiting from the low temperature synthesis. The optical performance of the QDs could be well persisted even in the moisture environment. Finally, the as-prepared QDs@SiO2 composite was fabricated as the QD ink on the anti-counterfeit printing technology, from which the obtained pattern would emit varied color under UV lamp. And the as-prepared composites was also applied for fabricating WLED, with Commission Internationale de l'Eclairage (CIE) color coordinates of (0.33, 0.38) and power efficiency of 32.5 lm W −1, demonstrating their promising potentials in solid-state lighting.